Migration strategies of the crisis-stricken youth in an enlarged European Union - Kahanec, Martin; Fabo, Brian (Bratislava, 2013)
"This paper studies the migration response of the youth from new EU member states to disparate conditions in an enlarged European Union at the onset of the Great Recession. We use the Eurobarometer data and probabilistic econometric models to identify the key drivers of the intention to work in another member state of European Economic Area (EEA) and their expected duration. We find that migration intentions are high among those not married and among males with children, but both categories are also overrepresented among people with only temporary as opposed to long-term or permanent migration plans. Whereas age affects migration intentions negatively, education has no effect on whether working abroad is envisaged. However, conditional on envisaging to work abroad, completion of education (if after 16th birthday) is associated with long-term (at least five years), but not permanent, migration plans. Finally, we find that socio-demographic variables explain about as much variation of migration intentions as self-reported push and pull factors and migration constraints."